Electrochemical Mechanism of the Preparation of High-Purity Indium by Electrodeposition - Hou, Zhongmin; Wang, Xiaomin; Li, Jidong; Li, Zhen; Wang, Yiyong; Xing, Hongxuan (Frontiers in Chemistry, 2022)
Indium is a crucial material to support the development of high-tech industries, and electrodeposition is an efficient method to recover rare metal resources. In this paper, an electrolyte containing indium sulfate and sodium sulphate, where the electrochemical behavior of In3+ was investigated. Cyclic voltammetry (CV), chronoamperometry (CA), and alternating current impedance (EIS) were used to investigate the reduction reaction of In3+ and the electrocrystallization mechanism of indium in the indium sulfate system. Cyclic voltammetry results showed that the electrodeposition process is irreversible. The average charge transfer coefficient a of In3+ was calculated from the relationship between the cathodic peak potential and the half-peak potential as 0.116, and the H+ discharge occurred at the higher negative potential of In3+. The nucleation mechanism of indium electrodeposition was analyzed by chronograph amperometry. The mechanism of indium at potential steps of -0.3 to -0.6 V was close to diffusion-controlled instantaneous nucleation with a diffusion coefficient of 7.31 × 10-9 cm2s-1.The EIS results demonstrated that the reduction process of In3+ is subject to a diffusion-controlled step when pH = 2.5 and the applied potential was -0.5 V. SEM and XRD indicated that the cathodic products deposited on the titanium electrode have excellent cleanliness and purity.